Critical Thinking Skills Mapping of State Junior High School Students Throughout the City of Surabaya Through Critical and Independent Learning Design - Hasyim, Faiz (Phi: Jurnal Pendidikan Fisika dan Terapan, 2024)
Critical Thinking Skills (CTS) are one of the most significant skills in the 21st century. Students as potential superior human resources must have high CTS, because those who have high CTS can effectively solve problems. This study defines the mastery of Junior High School students’ CTS throughout the city of Surabaya. The form of this study was quantitative descriptive. The subjects in this study were 74 students from 3 State Junior High Schools with high, medium, and low levels in Surabaya. Students' CTS was measured using a Critical Thinking Skills Test that has been developed previously thus its validity is guaranteed and it is suitable to be used in measuring Junior High School students' mastery of CTS. The results of the study showed that the critical thinking skills of high-level Junior High School students were in the high CTS category with an n-gain score of 0,73, the medium-level State Junior High School students were in the high CTS category with an n-gain score of 0,71, and the low-level State Junior High School students were in the medium CTS category with an n-gain score of 0.70. The average increase in the CTS of Junior High School students in Surabaya was in the high CTS category with an average n-gain score of 0,71. This research is expected to be a recommendation for education policy-makers in Surabaya regarding the learning design used, thus the CTS of Junior High School students in Surabaya can increase at all levels.